Blood oxygen affinity increases during digestion in the South American rattlesnake, Crotalus durissus terrificus - Bovo, Rafael P. [UNESP]; Fuga, Adriana [UNESP]; Micheli-Campbell, Mariana A. [UNESP]; Carvalho, José E.; Andrade, Denis V. [UNESP] (Elsevier B. V., 2015)
Digesting snakes experience massive increases in metabolism that can last for many days and are accompanied by adjustments in the oxygen transport cascade. Accordingly, we examined the oxygen-binding properties of the blood in the South American rattlesnake (Crotalus durissus terrificus) during fasting and 24 and 48h after the snakes have ingested a rodent meal corresponding to 15% (±2%) of its own body mass. In general, oxygen-hemoglobin (Hb-O2) affinity was significantly increased 24h post-feeding, and then returned toward fasting values within 48h post-feeding. Content of organic phosphates ([NTP] and [NTP]/[Hb]), hemoglobin cooperativity (Hill's n), and Bohr Effect (ΔlogP50/ΔpH) were not affected by feeding. The postprandial increase in Hb-O2 affinity in the South American rattlesnake can be almost entirely ascribed by the moderate alkaline tide that follows meal ingestion. In general, digesting snakes were able to regulate blood metabolites at quite constant levels (e.g., plasma osmolality, lactate, glucose, and total protein levels). The level of circulating lipids, however, was considerably increased, which may be related to their mobilization, since lipids are known to be incorporated by the enterocytes after snakes have fed. In conclusion, our results indicate that the exceptional metabolic increment exhibited by C. d. terrificus during meal digestion is entirely supported by the aerobic pathways and that among the attending cardiorespiratory adjustments, pulmonary Hb-O2 loading is likely improved due to the increment in blood O2 affinity.
Keywords: Blood oxygen transport; Feeding; Hb–o(2) affinity; Oxygen-binding properties; Postprandial; Reptile; Viperidae